Maternal phthalate and phthalate alternative metabolites and urinary biomarkers of estrogens and testosterones across pregnancy - Diana C. Pacyga; Joseph C. Gardiner; Jodi A. Flaws; Zhong Li; Antonia M. Calafat; Susan A. Korrick; Susan L. Schantz; Rita S. Strakovsky (Environment International, 2021)
Background/objectives: Pregnant women are ubiquitously exposed to phthalates from food packaging materials and personal care products. Phthalates alter estrogen and testosterone concentrations in experimental models, but their ability to impact these hormones in human pregnancy is not well characterized. Methods: We recruited women ages 18–40 into the Illinois Kids Development Study (I-KIDS) in early pregnancy. Participants provided up to 5 first-morning urine samples across pregnancy (8–40 weeks gestation) that we pooled for quantification of 19 phthalate or phthalate alternative metabolites. Either individual (ng/mL) or molar sums (nmol/mL) of metabolites were used as exposure biomarkers. We summed urinary concentrations (ng/mL) of eight major estrogen (SumEstrogens) and two major testosterone (SumTestosterones) metabolites measured at median 13, 28, and 34 weeks gestation. We also estimated the ratio of estrogens-to-androgens. Linear mixed-effects models assessed relationships of phthalates/alternatives as continuous measures or as concentration quartiles with SumEstrogens, SumTestosterones, and the Estrogen/Androgen ratio in 434 women. In our models, we controlled for age, race, education, parity, smoking in the first trimester, pre-pregnancy body mass index, diet quality, conception season, fetal sex, and gestational age at hormone assessment. We also explored whether gestational age at hormone assessment or fetal sex modified these associations. All biomarkers and outcomes were specific gravity-adjusted, and continuous exposures and outcomes were also natural log-transformed. Results: Most participants were non-Hispanic white (80.9%), college educated (82.2%), and had urinary phthalate/alternative metabolite concentrations similar to those of reproductive-aged U.S. women. Overall, select phthalate metabolites were positively associated with SumEstrogens and SumTestosterones, but negatively associated with the Estrogen/Androgen ratio. For example, SumEstrogens was 5.1% (95%CI: 1.8, 8.5) higher with every 2-fold increase in sum of di(2-ethylhexyl) phthalate metabolites, while SumTestosterones was 7.9% (95%CI: 1.0, 15.3) higher and Estrogen/Androgen ratio was −7.7% (95%CI: −13.6, −1.4) lower with every 2-fold increase in monoethyl phthalate. However, phthalate alternatives were only positively associated with SumEstrogens, which was 2.4% (95%CI: 0.4, 4.5) and 3.2% (95%CI: 0.7, 5.8) higher with every 2-fold increase in sum of di(isononyl) cyclohexane-1,2-dicarboxylate metabolites and sum of di(2-ethylhexyl) terephthalate metabolites, respectively. Gestational age- and fetal sex-specific associations were only consistently observed for associations of phthalates/alternatives with SumEstrogens, where associations were strongest in mid-to-late pregnancy in women carrying females. Conclusion: Phthalates/alternatives may impact gestational hormones, with potential for gestational age- and fetal sex-specific associations. Whether maternal urinary estrogens and testosterones mediate associations of phthalates/alternatives with pregnancy and fetal outcomes merits further investigation.